USM WINS FIRST GOLD MEDAL AT SUKIPT 2016 THROUGH KARATE-DO - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SKUDAI, 1 February 2016 – Universiti Sains Malaysia (USM) today bagged its first gold medal at the Higher Education Institutions Sports Championship (SUKIPT) 2016, hosted by Universiti Teknologi Malaysia (UTM) here, through Karatedo.